2021
DOI: 10.1055/a-1684-0448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiomerically Pure Oxa[9]helicene Derivatives by a Nucleophilic Cyclodehydration Reaction of Helical 1,1′-Bibenzo[c]phenanthrenylidene-2,2′-dione

Abstract: Enantiomerically pure 9-substituted 11-oxa[9]helicene derivatives have been synthesized through furan-ring formation by a nucleophilic cyclodehydration reaction of enantiomerically pure helical polycondensed 2,2′-diphenoquinone derivatives (1,1′-bibenzo[c]phenanthrenylidene-2,2′-diones). (P)-2,2′-diphenoquinone derivatives afforded (P)-oxa[9]helicenes, whereas (M)-2,2′-diphenoquinone derivatives afforded the corresponding (M)-oxa[9]helicenes. Therefore, the ring-closing reaction afforded the corresponding enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Notably, the remarkably high ( P / M ) enantiomerization barrier for OH9 contributed to the exceptional thermal stability of its enantiomers, observed when solutions of ( M )‐ OH9 were heated at 150 °C for 2 hours without any racemization. These results also compare well with the experimentally determined enantiomerization barrier of ( P )‐ OH9 (~40 kcal mol −1 ) as reported by Hossain and Karikomi using an Eyring plot 70 …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, the remarkably high ( P / M ) enantiomerization barrier for OH9 contributed to the exceptional thermal stability of its enantiomers, observed when solutions of ( M )‐ OH9 were heated at 150 °C for 2 hours without any racemization. These results also compare well with the experimentally determined enantiomerization barrier of ( P )‐ OH9 (~40 kcal mol −1 ) as reported by Hossain and Karikomi using an Eyring plot 70 …”
Section: Resultssupporting
confidence: 90%
“…CD spectra of isolated enantiomers ( P / M )‐ OH7 and ( P / M )‐ OH9 in chloroform solutions (1 × 10 −5 M) were measured (Figure 6A). To assign the configuration of each isomer, we compared the obtained CD spectra to those derived from TD‐DFT calculations (refer to Supporting Information) and the previously reported CD spectra of OH9 by Hossain and Karikomi 70 . The absolute configurations in the first and second fractions of the chiral HPLC analysis were designated as the ( P )‐ and ( M )‐enantiomers, respectively, for both OH7 and OH9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] The introduction of heteroatoms into ortho-fused polycyclic arrangements significantly changes the electronic structure and helps improve a variety of optoelectrical properties. [3] In our previous studies, we reported the synthesis of functionalized or substituted oxa [9]helicene derivatives in racemic and enantiomerically pure forms by the reaction of various nucleophilic reagents [4] (such as Lawesson's reagent, phosphorus pentasulfide, [5] alcohols, [6] thiols, [7] and some halogenating reagents [8] ) with helical quinone derivatives 1 (Scheme 1). [9] However, when aliphatic primary amines were used as nucleophilic reagents, it was found that, unlike in the case of other nucleophilic reagents [4][5][6][7][8] , an amide derivative 2 composed of a sevenmembered ring was formed through the insertion of amines into helical cyclohexadienone rings.…”
mentioning
confidence: 99%